Conservation of a Neutralization Epitope of Human T-cell Leukemia Virus Type 1 (HTLV-1) among Currently Endemic Clinical Isolates in Okinawa, Japan - Mariko Mizuguchi; Yoshiaki Takahashi; Reiko Tanaka; Takuya Fukushima; Yuetsu Tanaka (Pathogens, 2020)
Approximately one-tenth of the 10 million individuals living with human T-cell leukemia virus type-1 (HTLV-1) worldwide live in Japan. Most of these infected individuals live in the southwest region of Japan, including Okinawa prefecture; however, currently no prophylactic vaccine against HTLV-1 infection is available. For preventing the HTLV-1 spread, we previously generated a humanized monoclonal antibody (hu-LAT-27) that mediates both neutralization and antibody-dependent cellular cytotoxicity (ADCC). The neutralization epitope of LAT-27 is a linear amino acid sequence from residue 191 to 196 (Leu-Pro-His-Ser-Asn-Leu) of the HTLV-1 envelope gp46 protein. Here, we found that the LAT-27 epitope is well conserved among HTLV-1 clinical isolates prevalent in Okinawa. The hu-LAT-27 treatment inhibited syncytium formation by these clinical HTLV-1 isolates. Although an amino acid substitution at residue 192 in the LAT-27 epitope from proline to serine was found in a few HTLV-1 isolates, hu-LAT-27 could still react with a synthetic peptide carrying this amino acid substitution. These findings demonstrate the wide spectrum of hu-LAT-27 reactivity, suggesting that hu-LAT-27 may be a candidate drug for prophylactic passive immunization against HTLV-1 infection.